Endophoric definiteness: An analysis based on Romanian data - Keturakis, Antanas (Kalbotyra, 2018)
[full article and abstract in English] Definiteness as a grammatical or pragmatic category is usually explained via the act of reference. In this spirit, a definite noun phrase is said to ensure that the hearer can identify the entity to which the NP refers, thus establishing a successful act of communication. The well-known typology of definiteness types developed by Hawkins (1978) relies on this assumption. However, such an explanation fails to clarify all the definite noun phrases in discourse. This paper argues that the information provided in the complex nominal constituent can yield a definite interpretation of the nominal regardless of the hearer’s ability to identify the real-life referent to which the noun refers. Such types of definite noun phrases are subsumed in this article under the term “endophoric definiteness”. I will discuss two subtypes of endophoric definiteness. First, the relational definiteness, based on the notion of reference-point constructions will be discussed. Then I will turn to modificational definiteness where the use of modifiers contribute to the definite interpretation of the nominal. The article focuses on how the endophoric definiteness types function and what strategies can be used to mark them formally. To illustrate this point, I use the qualitative analysis of Romanian data. It shows that a language may have different grammatical patterns for the two subtypes of endophoric definiteness. This formal distinction in linguistic expression shows that relational and modificational definiteness types must be taken into account as contributing, in distinct ways, to the category of definiteness.